Hydrogenation catalysts for coal liquefaction oil, their preparation methods and applications, and methods for hydrotreating coal liquefaction oil.

CN122937815APending Publication Date: 2026-10-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510454665.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]上述方法在制备氧化钛-氧化铝复合氧化物载体时,流程复杂,生产过程不连续,引入TiO2的方法多为含钛有机试剂,成本较高,不适合工业化生产

Benefits of technology

[0018]本发明提供的催化剂,选用具有特定晶型、较高孔集中度以及有效孔孔径占比的载体与活性金属相互配合,催化剂具有较高的加氢反应活性,将其用于煤液化油加氢处理中,能够提高脱氮和脱芳烃性能,所得的加氢产品的供氢性能优异,具有更高的产品氢含量;进一步地,催化剂中羟基总含量在特定范围内,催化剂具有较低的极性,可避免芳烃分子强吸附在催化剂表面无法及时加氢脱氮进而导致积炭失活。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to the field of catalysts for coal liquefaction oil, and discloses a hydrogenation catalyst for coal liquefaction, its preparation method and application, and a method for hydrogenating coal liquefaction oil. The hydrogenation catalyst for coal liquefaction oil includes a support, an active metal supported on the support, and an additive. The support is a composite oxide containing alumina and titanium oxide, with the titanium oxide existing in anatase form. The active metal includes Group VIII and Group VIB metals. The pore density A of the support is 0.63-3.2. In the support, pores with a diameter of 4-20 nm account for 86-100% of the total pore volume. The 3240 cm⁻¹ infrared spectrum of the catalyst... ‑1 -3800cm ‑1 The integral peak area is I, where I represents the total hydroxyl content, and the I value is 0-2. This catalyst exhibits excellent hydrogenation reactivity, can improve the hydrodenitrogenation and dearomatization performance of coal liquefaction oil, and has a higher product hydrogen content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of catalysts for coal liquefaction oil, specifically to a hydrogenation catalyst for coal liquefaction oil, its preparation method and application, and a method for hydrogenation treatment of coal liquefaction oil. Background Technology

[0002] The whole-fraction oil from a coal liquefaction unit undergoes pre-hydrogenation treatment using T-star fluidized bed technology. The qualified hydrogen-donating solvent is then used to prepare coal-oil slurry. The unit providing this hydrogen-donating solvent is called a hydrogenation stabilization unit. The solvent used in coal liquefaction is a component separated from the liquefaction products. After hydrogenation stabilization, it acquires hydrogen-donating capacity and is therefore called a circulating solvent. Simultaneously, the circulating solvent also serves as a slurry preparation medium for fresh coal. After preheating, it returns to the liquefaction reaction section, directly or indirectly participating in the liquefaction reaction. Selecting a suitable circulating solvent can effectively dissolve, swell, dilute, and disperse coal particles, ensuring a relatively homogeneous hydrogen-liquid-solid three-phase reaction system. This is beneficial for coal-oil slurry transportation, preheating, coal thermal cracking, hydrogenation, and coking inhibition. The hydrogen-donating capacity of the solvent used in direct coal liquefaction directly affects the yield of liquid products. Given the crucial role of the hydrogenation stabilization process in direct coal liquefaction, developing a high-efficiency coal liquefaction oil fluidized bed hydrogenation stabilization catalyst has significant economic and social benefits.

[0003] Coal direct liquefaction oil has a high nitrogen content, low sulfur content, and a relatively high aromatic hydrocarbon content. The challenge in coal liquefaction oil development lies in achieving the removal of heteroatoms, especially nitrogen atoms, while simultaneously saturating tricyclic, tetracyclic, and higher-order aromatic hydrocarbons into tetrahydronaphthalenes or bicyclic alkylbenzenes, which have strong hydrogen-donating capabilities. Therefore, the development of catalytic materials requires, on the one hand, suitable pore structure, and on the other hand, weak adsorption performance for aromatic hydrocarbons to prevent them from failing to desorb in time after adsorption, leading to coking and deactivation.

[0004] Patent application CN113649016A describes a process where alumina, metatitanic acid, and a solvent are mixed, high-energy ball-milled, shaped, dried, and calcined to obtain a titanium oxide-alumina support. The titanium oxide-alumina composite support is then impregnated with a solution containing molybdenum and cobalt or nickel, followed by drying and calcination to obtain a hydrogenation catalyst. The hydrogenation catalyst prepared by this method exhibits advantages such as high low-temperature activity, as well as good hydrogenation activity and stability at high space velocities.

[0005] Patent application CN109833891A discloses a heavy distillate oil hydrotreating catalyst and its application using mesoporous TiO2-Al2O3 as a support. A mesoporous alumina precursor is prepared using a template-directed method. Titanium oxide, titanium isopropoxide, or tetrabutyl titanate is then introduced into the precursor solution. After crystallization and drying, a mesoporous TiO2-Al2O3 precursor is obtained. This precursor is mixed with alumina, an extrusion aid, and phosphate, extruded into strips, and then dried and calcined to obtain a phosphorus-modified TiO2-Al2O3 support. The catalyst's active components include Group VIB metal oxides, Group VIII oxides, and Group VA oxides. This method can prepare a mesoporous TiO2-Al2O3 support, effectively improving the catalyst's desulfurization and denitrification capabilities.

[0006] Patent application CN1344586A discloses a supported nano-TiO2 composite support and its preparation method. This method involves preparing a titanium sol by mixing tetrabutyl titanate with ethanol, water, and nitric acid. The titanium sol is then added to a slurry prepared by mixing boehmite with water or anhydrous ethanol. The sample is dried and calcined sequentially at 200, 300, 400, and 500 °C for 2 hours. This method can support nano-TiO2 on macroporous alumina. XRD results show that the nano-TiO2 has anatase crystal structure. Loading active components onto this support can effectively improve the hydrorefining catalytic activity of the catalyst.

[0007] The above methods are complex and discontinuous in preparing titanium oxide-alumina composite oxide supports. The methods for introducing TiO2 mostly involve titanium-containing organic reagents, which are costly and not suitable for industrial production. Summary of the Invention

[0008] The purpose of this invention is to overcome the problems existing in the prior art and provide a hydrogenation catalyst for coal liquefaction oil, its preparation method and application, and a method for hydrogenation treatment of coal liquefaction oil. This catalyst has excellent hydrogenation reaction activity, can improve the hydrogenation and denitrification performance of coal liquefaction oil, and has a higher product hydrogen content.

[0009] To achieve the above objectives, a first aspect of the present invention provides a hydrogenation catalyst for coal liquefaction, wherein the catalyst comprises a support and an active metal and an additive supported on the support, the support being a composite oxide comprising alumina and titanium oxide, wherein the titanium oxide exists in the form of anatase; the pore concentration A of the support is 0.63-3.2; in the support, pores with a diameter of 4-20 nm account for 86-100% of the total pore volume; the active metal comprises Group VIII and Group VIB metal elements; the additive is selected from at least one of phosphorus, silicon, and fluorine; and the 3240 cm⁻¹ infrared spectrum of the catalyst... -1 -3800cm -1The area of ​​the integral peak is I, where I represents the total hydroxyl content, and the value of I is 0.01-2.

[0010] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst for coal liquefaction, wherein the method includes the following steps:

[0011] (1) A gelling reaction is carried out between an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum to obtain a solid gelling product;

[0012] (2) In the presence of a precipitant, the solid gelling product obtained in step (1) is subjected to an aging reaction to obtain an aging reaction product.

[0013] (3) The aging reaction product obtained in step (2) is subjected to hydrothermal treatment and then subjected to first drying to obtain titanium-containing pseudoboehmite. The temperature of hydrothermal treatment is higher than the temperature of aging reaction.

[0014] (4) The titanium-containing pseudoboehmite obtained in step (3) is optionally shaped, and then subjected to a second drying and a first calcination to obtain a carrier, wherein the carrier is a composite oxide containing alumina and titanium oxide, wherein the titanium oxide exists in the form of anatase, and the first calcination is carried out in a water-containing atmosphere.

[0015] (5) The active metal and the additive are introduced onto the carrier obtained in step (4), and then a third drying and a second calcination are performed; the active metal includes Group VIII metal elements and Group VIB metal elements; the additive is selected from at least one of phosphorus, silicon and fluorine; the second calcination is performed under vacuum conditions.

[0016] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect in the hydrotreating of coal liquefaction oil.

[0017] A fourth aspect of the present invention provides a method for hydrotreating coal liquefaction oil, wherein the method includes: performing a hydrosaturation reaction on residual oil in the presence of a catalyst and hydrogen, wherein the catalyst is the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect.

[0018] The catalyst provided by this invention uses a support with a specific crystal form, high pore concentration, and effective pore size ratio in combination with an active metal. The catalyst has high hydrogenation reactivity. When used in the hydrogenation treatment of coal liquefaction oil, it can improve denitrification and dearomatics performance. The resulting hydrogenated product has excellent hydrogen supply performance and higher product hydrogen content. Furthermore, the total hydroxyl content in the catalyst is within a specific range, and the catalyst has low polarity, which can avoid strong adsorption of aromatic molecules on the catalyst surface, preventing timely hydrogenation and denitrification, thus avoiding carbon deposition and deactivation.

[0019] The method provided by this invention uses a combination of co-precipitation and hydrothermal methods to prepare a support containing alumina and titanium oxide composite oxides with low titanium oxide content and a specific crystal form without the use of organic titanium-containing reagents. This method is more conducive to the industrial production of hydrogenation catalysts and improves the hydrogenation and denitrification performance of the catalysts. Furthermore, the method provided by this invention has a simple process, uses inexpensive and readily available raw materials, easily controls operating conditions, and allows for adjustable product properties. In addition, by controlling the calcination conditions of the first and second calcinations, it has the advantages of high active metal dispersion and low catalyst surface polarity. Attached Figure Description

[0020] Figure 1 These are the XRD patterns of the carriers in Example 1 and Comparative Example 2. Detailed Implementation

[0021] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0022] The first aspect of this invention provides a hydrogenation catalyst for coal liquefaction, wherein the catalyst comprises a support and an active metal and an additive supported on the support, the support being a composite oxide comprising alumina and titanium oxide, wherein the titanium oxide exists in the form of anatase; the pore concentration A of the support is 0.63-3.2; in the support, pores with a diameter of 4-20 nm account for 86-100% of the total pore volume; the active metal comprises Group VIII and Group VIB metal elements; the additive is selected from at least one of phosphorus, silicon, and fluorine; the 3240 cm⁻¹ infrared spectrum of the catalyst... -1 -3800cm -1 The area of ​​the integral peak is I, where I represents the total hydroxyl content, and the value of I is 0.01-2.

[0023] The catalyst provided by this invention uses a support with a specific crystal form, high pore concentration, and pore size ratio in combination with an active metal. The catalyst has high hydrogenation reactivity. When used in the hydrogenation treatment of coal liquefaction oil, it can improve the denitrification and dearomatics performance. The hydrogen supply performance of the resulting hydrogenated product is superior to that of existing catalysts. Furthermore, the total hydroxyl content in the catalyst is within a specific range, and the catalyst has low surface polarity. In contrast, the I value of hydrogenation catalysts in the prior art is usually greater than 2, which has high adsorption performance for nitrogen-containing compounds or aromatics. Aromatic molecules are strongly adsorbed on the catalyst surface and cannot be hydrogenated and denitrified in time, leading to carbon deposition and deactivation.

[0024] In this invention, the I value was measured using an infrared method. Specific testing conditions were as follows: a Nicolet 6700 Fourier transform infrared spectrometer was used, with a DTGS detector; the sample was prepared as a self-supporting sheet, and the pretreatment conditions were 1.0 × 10⁻⁶. -3 At 450℃ for 2 hours, the sample temperature was allowed to drop to room temperature. The IR-OH spectrum was then measured, and the catalyst 3240 cm⁻¹ was calculated. -1 up to 3800cm -1 The peak area is calculated and applied to each mg of catalyst. The result is called the I value of the catalyst. The higher the I value, the higher the total amount of hydroxyl groups on a unit mass of catalyst.

[0025] In this invention, from Figure 1 The XRD pattern shows that titanium oxide exhibits diffraction peaks at 25.3°, 48.1°, 54°, and 55.1°, which belong to the anatase crystal form, indicating that titanium oxide exists in the support in the form of anatase.

[0026] In this invention, an SAP2420 automated adsorption analyzer manufactured by Micromerities Instruments, Inc. (USA) was used to determine the specific surface area and pore structure of the carrier using the N2 static low-temperature adsorption capacity method. Before testing, the sample required pretreatment under vacuum at 350℃ for 10 hours, followed by contact with the N2 adsorbate at 196℃ to achieve static adsorption equilibrium. The amount of N2 adsorbed by the sample was calculated from the difference between the N2 inlet gas rate and the amount remaining in the gas phase after adsorption. The surface area was calculated using the BET formula. The pore concentration was defined as follows: pore concentration (P0) was defined as the highest DV value (DV) in the BET pore size distribution-DV curve. MAX The ratio of the peak width at half maximum (FWHM) to the peak width at half maximum (P0 = DV) is called P0 = DV. MAX / FWHM.

[0027] In this invention, preferably, the catalyst has an infrared spectrum at 3240 cm⁻¹ -1 -3800cm -1 The area of ​​the integral peak is I, where I represents the total hydroxyl content, and the value of I is 0.3-0.6, for example, it can be 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, or 0.6. The advantage of this preferred embodiment is that it can avoid the strong adsorption of nitrogen-containing molecules or aromatic molecules in coal liquefaction oil on the catalyst surface, which would lead to catalyst coking and deactivation.

[0028] In this invention, preferably, the atomic ratio n of the total amount of Group VIII metal elements to the total amount of Group VIII and Group VIB metal elements in the catalyst is 0.01-0.25, more preferably 0.05-0.18, for example, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, or 0.18. The advantage of this preferred embodiment is that it controls the hydrogenation saturation activity of the catalyst for aromatic molecules within a specific range, avoiding the supersaturation hydrogenation of aromatic molecules into cycloalkanes, thereby reducing the hydrogen supply performance of the hydrogenated product.

[0029] In this invention, preferably, the wear rate of the catalyst is 0-0.2%, more preferably 0.01-0.05%.

[0030] In this invention, the catalyst wear rate is determined using the Q / SH 3360 246-2014 standard.

[0031] In this invention, the pore concentration A of the support is 0.65-2. The advantage of this preferred embodiment is that it ensures the effective activity of the catalyst and improves hydrogenation performance.

[0032] In this invention, preferably, in the carrier, pores with a diameter of 4-20 nm account for 90-100% of the total pore volume.

[0033] In this invention, preferably, the pores with a diameter of 4-8 nm account for 60-100% of the total pore volume in the support, more preferably 70-98%. The advantage of this preferred embodiment is that it ensures the effective activity of the catalyst and improves hydrogenation performance.

[0034] In this invention, preferably, the specific surface area of ​​the carrier is 100-400 m². 2 / g, preferably 180-300m 2 / g.

[0035] In this invention, preferably, the pore volume of the carrier is 0.4-1.3 mL / g, more preferably 0.5-1.2 mL / g.

[0036] In this invention, preferably, the pore diameter of the carrier is 4-13 nm, more preferably 8-12 nm.

[0037] In this invention, preferably, the alumina exists as γ-Al2O3.

[0038] In this invention, preferably, based on the total amount of the support, the alumina content is 70-99% by weight and the titanium oxide content is 1-30% by weight; more preferably, based on the total amount of the support, the alumina content is 75-96% by weight and the titanium oxide content is 4-25% by weight. The catalyst provided by this invention, using a support with low titanium content and containing anatase-type titanium oxide, has the advantage of high selective hydrogenation activity.

[0039] In this invention, it should be noted that a small amount of impurities may be present in the alumina-titanium oxide composite oxide carrier. Therefore, when impurities are present, the sum of the contents of alumina, titanium oxide, and the impurities must equal 100%. In this invention, the type of impurities is not specifically limited; for example, they can be SO3, Na2O, etc.

[0040] In this invention, the characteristic spectral lines of each element are determined by an X-ray fluorescence spectrometer of Rigaku Electric Industries, Ltd. of Japan, and the content of each component in the carrier is determined by semi-quantitative analysis using the external standard method.

[0041] In this invention, preferably, based on the total amount of the catalyst and calculated as oxides, the content of the Group VIII metal element is 0.5-10% by weight, preferably 1.5-5% by weight, the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight, and the content of the additive is 0.1-10% by weight.

[0042] In this invention, preferably, the Group VIII metal element is cobalt and / or nickel.

[0043] In this invention, preferably, the Group VIB metal element is molybdenum and / or tungsten.

[0044] In this invention, the content of each component in the catalyst was determined by XRF fluorescence (RIPP133-90) method.

[0045] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst for coal liquefaction, wherein the method includes the following steps:

[0046] (1) A gelling reaction is carried out between an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum to obtain a solid gelling product;

[0047] (2) In the presence of a precipitant, the solid gelling product obtained in step (1) is subjected to an aging reaction to obtain an aging reaction product.

[0048] (3) The aging reaction product obtained in step (2) is subjected to hydrothermal treatment and then subjected to first drying to obtain titanium-containing pseudoboehmite. The temperature of hydrothermal treatment is higher than the temperature of aging reaction.

[0049] (4) The titanium-containing pseudoboehmite obtained in step (3) is optionally shaped, and then subjected to a second drying and a first calcination to obtain a carrier, wherein the carrier is a composite oxide containing alumina and titanium oxide, wherein the titanium oxide exists in the form of anatase, and the first calcination is carried out in a water-containing atmosphere.

[0050] (5) The active metal and the additive are introduced onto the carrier obtained in step (4), and then a third drying and a second calcination are performed; the active metal includes Group VIII metal elements and Group VIB metal elements; the additive is selected from at least one of phosphorus, silicon and fluorine; the second calcination is performed under vacuum conditions.

[0051] The method provided by this invention uses a combination of co-precipitation and hydrothermal methods to prepare an alumina-titanium oxide composite oxide with low titanium oxide content and a specific crystal form as a support without using organic titanium-containing reagents. This method is more conducive to the industrial production of hydrogenation catalysts. Furthermore, the raw materials are inexpensive and readily available, the operating conditions are easy to control, and the product properties are adjustable. Moreover, by controlling the calcination methods of the first and second calcinations, the low surface polarity of the catalyst can be reduced, and the dispersion of the active metal can be increased, resulting in a catalyst with excellent hydrogenation performance.

[0052] In this invention, there are no particular limitations on the preparation method of the acidic solution containing aluminum and titanium, as long as the titanium-containing compound can be dissolved in an aluminum solution to obtain the acidic solution. Preferably, in step (1), the acidic solution containing aluminum and titanium is prepared by dissolving the titanium-containing compound in an acidic aluminum solution.

[0053] In this invention, there is no particular limitation on the type of titanium-containing compound, as long as it meets the requirements of the gelation reaction. Preferably, the titanium-containing compound is titanium oxysulfate and / or titanium sulfate. By selecting titanium-containing compounds within the above range to prepare an acidic solution containing titanium and aluminum for the gelation reaction, the use of organic titanium reagents is avoided, ensuring that the entire preparation process is simple and environmentally friendly.

[0054] In this invention, there is no particular limitation on the type of acidic aluminum solution. Preferably, the acidic aluminum solution is selected from at least one of aluminum sulfate solution, aluminum nitrate solution, and aluminum chloride solution.

[0055] In this invention, there is no particular limitation on the type of aluminum-containing alkaline solution, as long as the gelation reaction is achieved. Preferably, in step (1), the aluminum-containing alkaline solution is a sodium aluminate solution and / or a potassium aluminate solution.

[0056] In this invention, the ratio of titanium to aluminum is controlled by adjusting the concentration of the acidic solution containing aluminum and titanium, thereby controlling the titanium content to prepare alumina-titanium oxide composite oxides in different ranges to meet different application scenarios. Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as alumina, is 35-120 g / L, for example, it can be 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, 110 g / L, 115 g / L, 120 g / L, or any value between any two groups.

[0057] In this invention, preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as titanium oxide, is 5-80 g / L. For example, it can be 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, or any value between any two groups.

[0058] In this invention, there is no particular limitation on the concentration of the aluminum-containing alkaline solution, as long as it meets the requirements of the gelation reaction. Preferably, in step (1), the concentration of the aluminum-containing alkaline solution, calculated as alumina, is 20-300 g / L, for example, it can be 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L, 250 g / L, 260 g / L, 270 g / L, 280 g / L, 290 g / L, 300 g / L, or any value between any two groups.

[0059] In this invention, preferably, the amounts of the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are such that, based on the total amount of the alumina-titanium oxide composite oxide carrier, the content of alumina is 70-99% by weight, preferably 75-96% by weight, and the content of titanium oxide is 1-30% by weight, preferably 4-25% by weight.

[0060] In this invention, in step (1), the temperature of the aging reaction is 5-50°C higher than the temperature of the gelation reaction, preferably 10-30°C higher.

[0061] In this invention, the method of gelation reaction is not particularly limited and can be any method conventionally defined in the art. Preferably, in step (1), the gelation reaction is carried out continuously or intermittently, preferably continuously. On the one hand, carrying out the gelation reaction continuously is more conducive to controlling the pH of the gelation reaction process, effectively improving the quality of the alumina-titanium oxide composite oxide. On the other hand, continuous operation can increase the throughput per unit time and improve production efficiency.

[0062] The present invention does not particularly limit the equipment used for the gelation reaction, and any conventional choice in the art can be used. Specifically, for example, it can be carried out in a gelation tank.

[0063] According to a preferred embodiment of the present invention, the continuous gelation reaction process of the present invention includes: adding a certain amount of deionized water to the gelation tank in advance, and introducing an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum from the top of the gelation tank, so that the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are mixed and contacted to carry out the gelation reaction, and the slurry generated by the gelation reaction flows out of the gelation tank continuously, while controlling the liquid level in the gelation tank to remain constant.

[0064] In this invention, the conditions for the gelation reaction are relatively flexible. Preferably, in step (1), the conditions for the gelation reaction include: a temperature of 40-80℃ and a pH value of 3-7; preferably, in step (1), the conditions for the gelation reaction include: a temperature of 50-70℃ and a pH value of 4-7. Under this preferred method, it is more beneficial to improve the quality of the alumina-titanium oxide composite oxide. In this invention, the pH value should not be too high during the gelation reaction, as an excessively high pH will result in low pore volume and specific surface area of ​​the composite oxide product; the pH value should also not be too low, as a low pH will easily lead to a large difference in the formation rate of hydrated oxides of aluminum and titanium, which is not conducive to the uniform dispersion of titanium in alumina. In this invention, there is no particular limitation on the method of pH control. For example, the flow rates of the acidic solution containing aluminum and titanium and the precipitant can be adjusted. In this invention, there is no particular limitation on the flow rates of the acidic solution containing aluminum and titanium and the precipitant, as long as the pH value of the gelation reaction is met.

[0065] In this invention, the pH value of the reaction system is adjusted by adding a precipitant, so that the slurry obtained from the solid gelling product in step (1) undergoes an aging reaction after pulping. This invention allows for a wide range of precipitant selection. Preferably, in step (2), the precipitant is selected from alkali metal compounds, and more preferably from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

[0066] In this invention, the selection range for the aging reaction conditions is relatively wide. Preferably, in step (2), the aging reaction conditions include: a temperature of 60-98℃, a time of 4-9h, and a pH value of 7-11; more preferably, in step (2), the aging reaction conditions include: a temperature of 70-95℃, a time of 5-8h, and a pH value of 7.5-10. By controlling the aging reaction conditions, the pore structure of the alumina-titanium oxide composite oxide is regulated, thereby improving the quality of the alumina-titanium oxide composite oxide.

[0067] In this invention, preferably, after the aging treatment, step (2) further includes solid-liquid separation of the aging product to obtain a solid aging product. In this invention, the solid-liquid separation is a conventional operation in the art, specifically, for example, it can be at least one of sedimentation, filtration and centrifugation, which can be selected by those skilled in the art according to actual needs.

[0068] In this invention, preferably, the hydrothermal treatment temperature is 10-100°C higher than the aging reaction temperature, more preferably 10-80°C higher, and even more preferably 20-70°C higher. By controlling the temperatures of the aging reaction and the hydrothermal treatment, the pore concentration of the alumina-titanium oxide composite oxide can be increased, while obtaining the anatase crystal form. When the temperature difference between the two is not within the above-mentioned preferred range, the alumina-titanium oxide composite oxide grain size is large, affecting the specific surface area and most probable pore size of the composite oxide material.

[0069] In this invention, preferably, before hydrothermal treatment, step (3) further includes washing the solid aging product. In this invention, the washing operation is a conventional operation in the art, requiring only a reduction in the content of impurity ions (e.g., residual sodium and sulfate) in the solid aging product, for example, such that the sodium oxide content in the obtained alumina-titanium oxide composite oxide is less than 0.1% by weight, preferably less than 0.06% by weight, and more preferably 0.01-0.05% by weight.

[0070] In this invention, preferably, step (3) includes: adding water (preferably deionized water) to the solid aging product after aging treatment, pulping it, and then performing hydrothermal treatment. In this invention, the amount of water used is such that the concentration of the slurry obtained after pulping, based on the weight of oxides (alumina + titanium oxide), is 50-180 g / L, preferably 70-150 g / L.

[0071] Provided that the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction, the selection range of the hydrothermal treatment conditions is relatively wide, in order to further optimize the pore structure characteristics of the alumina-titanium oxide composite oxide. Preferably, in step (3), the hydrothermal treatment conditions include: temperature 100-180℃, time 2-9h. Hydrothermal treatment can change the state of titanium dioxide on alumina. The combination of co-precipitation and hydrothermal methods not only improves the pore concentration of the alumina-titanium oxide composite oxide, making the most probable pore size fall within a suitable range, but also allows the titanium dioxide dispersed in the alumina framework to aggregate in the form of anatase, obtaining anatase-γ-Al2O3 support when the titanium dioxide content is low.

[0072] In this invention, preferably, no organic titanium-containing reagents are used in steps (1)-(3). This invention prepares alumina-titanium oxide composite oxides as a carrier via co-precipitation and hydrothermal treatment. The reaction process is simple, easy to operate, uses inexpensive and readily available raw materials, requires no organic reagents, and is environmentally friendly.

[0073] In this invention, the range of conditions for the first drying is relatively wide. Preferably, in step (3), the conditions for the first drying include a temperature of 60-200℃, more preferably 100-160℃.

[0074] In this invention, preferably, in step (4), the conditions for the first calcination include: a temperature of 100-1000℃, a time of 1-10h, and a water-to-carrier mass ratio of 0.1-10; preferably, in step (3), the conditions for the first calcination include: a temperature of 300-650℃, a time of 2-6h, and a water-to-carrier mass ratio of 0.5-3.5. In this invention, the "water-to-carrier mass ratio" refers to the mass ratio of water to the carrier in a water-containing atmosphere. The advantage of calcination in a water-containing atmosphere is that the active metal dispersion is high, which improves the hydrogenation performance.

[0075] In this invention, the first roasting is preferably carried out in a steam furnace or a roasting furnace in which steam can be introduced.

[0076] In this invention, preferably, in step (3), the aqueous atmosphere also contains air, preferably at a rate of 0.5-12 mL / (h·g), more preferably 0.6-8 mL / (h·g), and even more preferably 2-8 mL / (h·g). The advantage of this preferred embodiment is the high dispersion of the active metal.

[0077] In this invention, step (4) optionally means that during the mixing and molding process described in step (4), a glue solvent and an extrusion aid may be added, or no glue solvent and an extrusion aid may be added.

[0078] In this invention, the type of extrusion aid is not particularly limited, and any extrusion aid conventionally defined in the art is applicable to this invention. Preferably, the extrusion aid can be guar gum powder or cellulose, which can be selected by those skilled in the art according to conventional methods.

[0079] In this invention, the type of adhesive solvent is not particularly limited, and adhesive solvents conventionally defined in the art are all applicable to this invention. Preferably, the adhesive solvent can be at least one of nitric acid, citric acid, and hydrochloric acid, which can be selected conventionally by those skilled in the art.

[0080] The present invention does not impose any particular limitation on the amount of the adhesive solvent and the extrusion aid, and the amounts can be selected in accordance with conventional methods in the art to ensure smooth subsequent molding.

[0081] In this invention, water may or may not be added during the mixing process described in step (4). This invention does not impose any particular limitation on the amount of water used, as long as the subsequent molding process is successful.

[0082] The present invention does not particularly limit the molding method described in step (4), and can adopt the molding method commonly used in the art, such as at least one of extrusion molding, spray molding, roll forming and tablet forming.

[0083] In this invention, the conditions for the second drying are not particularly limited, and those skilled in the art can adjust them according to actual needs.

[0084] In this invention, preferably, in step (5), the conditions for the second calcination include: a temperature of 350-1000℃, a time of 1-10h, and a vacuum degree of -0.1MPa to -10MPa; more preferably, in step (5), the conditions for the second calcination include: a temperature of 400-650℃, a time of 2-6h, and a vacuum degree of -0.1MPa to -3MPa. Calcination under vacuum conditions can reduce the surface polarity of the catalyst and improve its hydrogenation performance.

[0085] In this invention, the second calcination is preferably carried out in a vacuum furnace or a calcination furnace that can be connected to a vacuum pump.

[0086] The present invention does not particularly limit the method for introducing the active metal, and various methods conventionally used in the art can be employed, such as impregnation and co-precipitation. Preferably, the active metal is introduced onto the support using the impregnation method.

[0087] In this invention, preferably, the method includes: impregnating a carrier in an impregnation solution containing a compound of a Group VIII metal element, a Group VIB metal element and an additive, followed by a third drying and a second calcination.

[0088] The present invention does not specifically limit the method of impregnation. The method of impregnation can be impregnation with excess liquid or impregnation with equal volume, depending on the amount of impregnation liquid used.

[0089] In this invention, preferably, the amounts of Group VIII and Group VIB metal elements are such that, based on the total amount of the catalyst, the content of the Group VIII metal element, calculated as oxide, is 0.5-10% by weight, preferably 1.5-5% by weight; and the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight.

[0090] In this invention, preferably, the Group VIII metal element is cobalt and / or nickel.

[0091] In this invention, preferably, the Group VIB metal element is molybdenum and / or tungsten.

[0092] The present invention allows for a wide range of choices of compounds containing Group VIII metal elements, which can be conventional choices in the art. Preferably, the compounds containing Group VIII metal elements are selected from at least one of the nitrates, acetates, carbonates, chlorides, and soluble complexes of Group VIII metal elements, such as cobalt nitrate, nickel nitrate, nickel acetate, cobalt acetate, cobalt chloride, nickel chloride, cobalt carbonate, nickel carbonate, cobalt citrate, and nickel citrate.

[0093] The present invention allows for a wide range of choices of compounds containing the Group VIB metal elements, which can be conventional choices in the art. Preferably, the compounds containing the Group VIB metal elements are selected from at least one of molybdates, tungstates, metatungstates, and ethyl metatungstates.

[0094] The present invention allows for a wide range of choices of compounds for the adjuvants. Preferably, the adjuvant compound can be phosphoric acid.

[0095] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect in the hydrotreating of coal liquefaction oil.

[0096] A fourth aspect of the present invention provides a method for hydrogenating coal liquefaction oil, wherein the method comprises: performing a hydrogenation reaction on coal liquefaction oil in the presence of a catalyst and hydrogen, wherein the catalyst is the catalyst described in the first aspect or a catalyst prepared by the preparation method described in the second aspect.

[0097] In this invention, preferably, the reaction conditions include: a temperature of 200-420℃, a pressure of 2-18 MPa, a hydrogen-to-oil volume ratio of 50-5000, and a liquid hourly space velocity of 0.1-10 h⁻¹. -1Preferably, the reaction conditions include: a temperature of 220-400℃, a pressure of 2-16 MPa, a hydrogen-to-oil volume ratio of 50-4000, and a liquid hourly space velocity of 0.15-6 h⁻¹. -1 .

[0098] The present invention does not impose any particular limitation on the hydrogenation device used in the hydrogenation reaction. It can be any reactor that is sufficient to allow coal liquefaction oil to contact the catalyst under the hydrogenation reaction conditions, such as a fixed bed reactor, a slurry bed reactor, a moving bed reactor, or a fluidized bed reactor. Those skilled in the art can select the appropriate device based on conventional experiments.

[0099] The present invention will be described in detail below through embodiments. Unless otherwise specified, all raw materials used in the following embodiments are commercially available products.

[0100] The composition of the titanium dioxide-alumina composite oxide carrier was determined by measuring the characteristic spectral lines of each element using a Rigaku Electric Co., Ltd. 3271 X-ray fluorescence spectrometer. The elemental content of the titanium dioxide-alumina composite oxide carrier was semi-quantitatively analyzed using the external standard method, yielding the composition of Al2O3, TiO2, SO3, Na2O, etc. in the sample.

[0101] The N2 adsorption-desorption characterization method is as follows: N2 adsorption-desorption characterization is performed on a Micromeritics ASAP 2420 adsorption instrument. Before the test, about 0.3g of composite oxide powder is taken and pretreated at 350℃ under vacuum for 10 hours.

[0102] The crystal form characterization method for titanium oxide and alumina in the support was as follows: A certain amount of titanium oxide-alumina composite oxide powder was pressed into sheets, and the crystal form of the sample was determined using a Philips XPERT series X-ray powder diffractometer. The test conditions were: Cu Kα rays (Kα = 0.154 nm), operating current 30 mA, operating voltage 40 kV, Ni filter, and scanning range 2θ = 5°-70°.

[0103] In this invention, the I value was measured using an infrared method. Specific testing conditions were as follows: a Nicolet 6700 Fourier transform infrared spectrometer was used, with a DTGS detector; the sample was prepared as a self-supporting sheet, and the pretreatment conditions were 1.0 × 10⁻⁶. -3 At 450℃ for 2 hours, the sample temperature was allowed to drop to room temperature. The IR-OH spectrum was then measured, and the catalyst 3240 cm⁻¹ was calculated. -1 up to 3800cm -1 The peak area is calculated and applied to each mg of catalyst. The result is called the I value of the catalyst. The higher the I value, the higher the total amount of hydroxyl groups on a unit mass of catalyst.

[0104] In this invention, the catalyst wear rate is determined using the Q / SH 3360 246-2014 standard.

[0105] In this invention, the content of each component in the catalyst was determined by XRF fluorescence (RIPP133-90) method.

[0106] Example 1

[0107] (1) Add 3L of deionized water to the gelling tank in advance, dissolve titanium oxysulfate in aluminum sulfate solution to obtain an acidic solution containing aluminum and titanium, and pass the acidic solution containing aluminum and titanium and sodium aluminate solution from the top of the gelling tank to mix the acidic solution containing aluminum and titanium and sodium aluminate solution in the gelling tank to carry out the gelling reaction. The slurry after the gelling reaction flows out from the overflow pipe of the gelling tank. The liquid level in the gelling tank remains unchanged. When the pre-added deionized water is replaced by the slurry after the gelling reaction, the slurry collection begins, and then the filter cake (solid gelling product) is obtained by filtration.

[0108] The concentration of sodium aluminate solution (calculated as alumina) was 200 g / L, and the flow rate was 42 g / min; the concentration of titanium oxide in the acidic solution was 12.89 g / L, and the concentration of alumina was 58 g / L. The flow rate of the acidic solution was adjusted to 115-125 g / min, the pH value of the gelation reaction was 6.3, and the temperature of the gelation reaction was 60℃.

[0109] (2) The gelation reaction product is subjected to aging treatment. The aging treatment conditions are pH 9.0, temperature 90℃, and time 6h. The aged product is added to deionized water and pulped to obtain an aged mixture. The concentration of the slurry is 70g / L based on titanium oxide-alumina.

[0110] (3) The aged mixture was filtered and washed sequentially to remove residual sodium and sulfate. The resulting filter cake was then added to deionized water and slurried. The concentration of the resulting slurry was 130 g / L (calculated as titanium dioxide-alumina). The resulting slurry was subjected to hydrothermal treatment at 150°C for 4 hours. After the hydrothermal step was completed, titanium-containing pseudoboehmite Al was obtained by spray drying. The final composition of Al after calcination at 600°C for 3 hours is listed in Table 1.

[0111] (4) Take 100g of titanium-containing pseudoboehmite A1 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 85ml of 1.65% nitric acid aqueous solution and mix evenly. Continue to knead the mixture into a plastic body on a twin-screw extruder, and then extrude it into a cylindrical strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, calcine it in a calcining furnace that can introduce steam at 580℃, with a water-to-agent mass ratio of 0.675 and an air flow rate of 6mL / (h·g) for 3 hours to obtain carrier Z1. The properties of carrier Z1 are shown in Table 1. The XRD pattern of carrier Z1 is shown in Table 1. Figure 1 As shown, from Figure 1 As can be seen, (titanium oxide exhibits diffraction peaks at 25.3°, 48.1°, 54°, and 55.1°, indicating that titanium oxide is in the anatase crystal form), while aluminum oxide exhibits the γ-Al₂O₃ crystal form (aluminum oxide exhibits diffraction peaks at 36°, 45°, and 67°, indicating that aluminum oxide is in the γ-Al₂O₃ crystal form).

[0112] (5) 100g of the support was impregnated with 80mL of a mixed aqueous solution consisting of molybdenum trioxide, basic nickel carbonate, and phosphoric acid (containing 486g / L MoO3, 36g / L NiO, and 68g / L phosphoric acid) for 1 hour, dried at 120℃ for 2 hours, and calcined at 400℃ in a vacuum furnace at a vacuum degree of -0.1MPa for 3 hours to obtain the hydrogenation catalyst C1. Based on the total weight of the catalyst, the contents of molybdenum oxide and nickel oxide in catalyst C1 were determined by X-ray fluorescence spectrometry (see Petrochemical Analytical Methods RIPP133-90 for specific methods). The results are shown in Table 2.

[0113] Comparative Example 1

[0114] This comparative example uses the preparation method described in the existing technical document (“Effects of the addition of titania onthethermal characterization of alumina-supported palladium”, Journal of Molecular Catalysis A, 2002, 180, 285-291) to prepare titanium dioxide-alumina composite oxide. 20 g of γ-Al₂O₃ (Sinopec Changling Catalyst Co., Ltd.) and 7.74 g of isopropyl titanate were dissolved in propanol, and the solution was diluted to 15 mL and stirred thoroughly. Subsequently, γ-Al₂O₃ was dispersed in the isopropyl titanate solution in isopropyl alcohol, dried overnight at 110 °C, and then calcined at 550 °C for 3 hours to obtain titanium dioxide-alumina composite oxide support S1. The final composition of titanium dioxide-alumina composite oxide support S1 is listed in Table 1. The XRD pattern of support S1 is shown below. Figure 1 As shown, from Figure 1It can be seen that in the titanium oxide-alumina composite oxide carrier S1, titanium oxide exhibits anatase crystal form, while alumina exhibits γ-Al2O3 crystal form as in Example 1.

[0115] Take 100g of support S1, and follow the same steps as in Example 1 to obtain catalyst DC2.

[0116] Example 2

[0117] Following the method of Example 1, in step (1), the concentration of titanium oxide in the acidic solution containing aluminum and titanium was 20.67 g / L, the concentration of aluminum oxide was 45.76 g / L, and the flow rate was 110-120 g / min. The remaining conditions were the same as in Example 1.

[0118] (2) Same as Example 1.

[0119] (3) The aged mixture was filtered and washed sequentially to remove residual sodium and sulfate. The resulting filter cake (solid aged product) was then added to deionized water and slurried. The concentration of the resulting slurry was 130 g / L based on the weight of the titanium dioxide-alumina composite oxide. The resulting slurry was hydrothermally treated at 150 °C for 4 h, filtered, and then dried at 120 °C for 6 h to obtain titanium-containing pseudoboehmite A2. The final composition of A2 after calcination at 600 °C for 3 h is listed in Table 1.

[0120] (4) Take 100g of titanium-containing pseudoboehmite A2 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 105ml of 1% nitric acid aqueous solution and continue to knead it into a plastic body on a twin-screw extruder. Then, extrude it into a butterfly strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, calcine it at 600℃ for 3 hours under the conditions of water-to-agent mass ratio of 1.0 and air flow rate of 6mL / (h·g) to obtain carrier Z2. The properties of carrier Z2 are shown in Table 1.

[0121] (5) Take 1000g of the support and impregnate it with 800mL of a mixed aqueous solution consisting of molybdenum trioxide, basic nickel carbonate, and phosphoric acid (containing 433g / L MoO3, 38g / L NiO, and 56g / L phosphoric acid) for 2 hours. Dry it at 120℃ for 3 hours and calcine it at 400℃ in a vacuum furnace at a vacuum degree of -0.5MPa for 3 hours to obtain the hydrogenation catalyst C2. Based on the total weight of the catalyst, the content of molybdenum oxide and nickel oxide in catalyst C2 was determined by X-ray fluorescence spectrometry (see Petrochemical Analytical Methods RIPP133-90 for specific methods). The results are shown in Table 2.

[0122] Example 3

[0123] Titanium-containing pseudoboehmite A3 was prepared according to the method of Example 2, with steps (1) and (2) being the same as in Example 2;

[0124] (3) The aged mixture was sequentially washed and filtered to remove residual sodium and sulfate. The resulting filter cake (solid aged product) was then added to deionized water and slurried. The concentration of the resulting slurry was 130 g / L based on the weight of the titanium dioxide-alumina composite oxide. The resulting slurry was hydrothermally treated at 130 °C for 4 h, filtered, and then dried at 120 °C for 6 h to obtain titanium-containing pseudoboehmite A3. The final composition of A3 after calcination at 600 °C for 3 h is listed in Table 1.

[0125] (4) Take 100g of titanium-containing pseudoboehmite A3 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 105ml of 2% nitric acid aqueous solution and continue to knead it into a plastic body on a twin-screw extruder. Then, extrude it into a butterfly strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, calcine it at 600℃ for 5 hours under the conditions of water-to-agent mass ratio of 1.2 and air flow rate of 2mL / (h·g) to obtain carrier Z3. The properties of carrier Z3 are shown in Table 1.

[0126] The remaining steps were the same as in Example 1, and catalyst C3 was obtained.

[0127] Example 4

[0128] According to the method of Example 2, steps (1) and (2) are the same as in Example 2;

[0129] (3) The aged mixture was filtered and washed sequentially to remove residual sodium and sulfate. The resulting filter cake (solid aged product) was then added to deionized water and slurried. The concentration of the resulting slurry was 130 g / L based on the weight of the titanium dioxide-alumina composite oxide. The resulting slurry was hydrothermally treated at 110 °C for 4 h to obtain titanium-containing pseudoboehmite A4. The final composition of A4 after calcination at 600 °C for 3 h is listed in Table 1.

[0130] (4) Take 100g of titanium-containing pseudoboehmite A4 and 3g of guar gum powder and mix them evenly. At room temperature, mix the mixture with 105ml of 2.5% nitric acid aqueous solution and mix evenly. Continue to knead the mixture into a plastic body on a twin-screw extruder and then extrude it into a butterfly strip with a diameter of 1.4 mm. After drying the wet strip at 120℃ for 4 hours, calcine it at 580℃ for 6 hours under the conditions of water-to-agent mass ratio of 1.0 and air flow rate of 3mL / (h·g) to obtain carrier Z4. The properties of carrier Z4 are shown in Table 1.

[0131] The remaining steps were the same as in Example 1, and catalyst C4 was obtained.

[0132] Example 5

[0133] The method is the same as in Example 1, except that in step (4), the water-to-agent mass ratio is 10 and the air flow rate is 10 mL / (h·g).

[0134] Example 6

[0135] The method is the same as in Example 1, except that in step (5), the vacuum furnace is kept at a vacuum level of -5 MPa.

[0136] Example 7

[0137] The method is the same as in Example 1, except that in step (3), the temperature of the hydrothermal treatment is 180°C.

[0138] Comparative Example 2

[0139] Titanium oxide-alumina composite oxide support S2 was obtained by the same impregnation method as Comparative Example 1. 20 g of γ-Al₂O₃ (Sinopec Changling Catalyst Co., Ltd.) and 15.48 g of isopropyl titanate were dissolved in propanol, and the solution was diluted to 15 mL and stirred thoroughly. Subsequently, γ-Al₂O₃ was dispersed in the above isopropyl titanate solution in isopropyl alcohol, dried overnight at 110 °C, and then calcined at 550 °C for 3 hours to obtain titanium oxide-alumina composite oxide support S2. The final composition of the composite oxide support titanium oxide-alumina S2 is listed in Table 1.

[0140] Take 100g of support S2, and follow the same steps as in Example 1 to obtain catalyst DC2.

[0141] Comparative Example 3

[0142] The method of Example 1 is different except that in step (3), the hydrothermal treatment temperature is 80°C, which is lower than the aging temperature of 90°C, to obtain carrier DZ3.

[0143] Comparative Example 4

[0144] The method is the same as in Example 1, except that in step (4), water vapor is not introduced during the calcination of the carrier molding to obtain carrier DZ4.

[0145] Comparative Example 5

[0146] The method is the same as in Example 1, except that in step (5), the catalyst is roasted in an atmospheric pressure tubular furnace instead of in a vacuum furnace.

[0147] The physicochemical parameters of the catalysts in the above embodiments and comparative examples are shown in Table 2.

[0148] Table 1

[0149]

[0150]

[0151] Note: In Table 1, the contents of Al2O3 and TiO2 are expressed in weight % (%).

[0152] Table 2

[0153]

[0154] Test case

[0155] The catalysts prepared in the above examples and comparative examples were subjected to coal liquefaction oil hydrogenation reaction.

[0156] The hydrogenation catalysts prepared in the above-mentioned 100 mL examples and comparative examples were crushed into particles with a diameter of 2-3 mm and then pre-sulfurized. The pre-sulfurization conditions included: using Jingmen Changyi No. 1 kerosene containing 5 wt% dimethyl disulfide as the sulfiding oil, and a liquid hourly space velocity (LHSV) of 1.2 h⁻¹ for the sulfiding oil. -1 The hydrogen partial pressure was 12.0 MPa, the hydrogen-to-oil volume ratio was 400, and the reaction was carried out at a constant temperature of 360℃ for 3 hours. Evaluation was then conducted in a 100 mL simulated fluidized bed reactor (catalyst loading: 100 mL). The feedstock was coal liquefaction oil (sulfur content: 89 μg / g, nitrogen content: 3200 μg / g, total aromatics content: 70.1 wt%), and the reaction was carried out at a reaction temperature of 380℃, a hydrogen partial pressure of 12.0 MPa, and a liquid hourly space velocity (LHSV) of 1.5 h⁻¹. -1 Hydrogenation activity performance was tested under the condition of a hydrogen-to-oil volume ratio of 400, and the test results are shown in Table 3.

[0157] The sulfur content in the oil sample was determined using the coulometric method (see RIPP 62-90 for details). The nitrogen content in the oil sample was determined using the chemiluminescence method (see RIPP SH0704-Z for details).

[0158] Table 3

[0159]

[0160] As can be seen from Table 3, the hydrogenation catalyst provided by this invention has a higher denitrification rate, a lower aromatic carbon ratio, a higher product hydrogen content, and a higher tetrahydronaphthalene content under the same conditions, thus exhibiting higher hydrogen supply performance.

[0161] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A hydrogenation catalyst for coal liquefaction oil, wherein, The catalyst comprises a support and an active metal and an additive supported on the support. The support is a composite oxide comprising alumina and titanium dioxide, wherein the titanium dioxide exists in the form of anatase. The pore concentration A of the support is 0.63-3.

2. In the support, pores with a diameter of 4-20 nm account for 86-100% of the total pore volume. The active metal includes Group VIII and Group VIB metals. The additive is selected from at least one of phosphorus, silicon, and fluorine. The 3240 cm⁻¹ infrared spectrum of the catalyst... -1 -3800cm -1 The area of ​​the integral peak is I, where I represents the total hydroxyl content, and the value of I is 0.01-2.

2. The catalyst according to claim 1, wherein, The catalyst's infrared spectrum is at 3240 cm⁻¹ -1 -3800cm -1 The area of ​​the integral peak at that point is I, where I represents the total hydroxyl content, and the value of I is 0.3-0.

6. And / or, in the catalyst, the atomic ratio n of the total amount of Group VIII metal elements to the total amount of Group VIII metal elements and Group VIB metal elements is 0.01-0.25, preferably 0.05-0.18; And / or, the attrition rate of the catalyst is 0-0.2%, preferably 0.01-0.05%.

3. The catalyst according to claim 1 or 2, wherein, The pore concentration A of the carrier is 0.65-2; And / or, in the carrier, pores with a diameter of 4-20 nm account for 90-100% of the total pore volume; And / or, in the carrier, pores with a diameter of 4-8 nm account for 60-100% of the total pore volume, preferably 70-98%; And / or, the specific surface area of ​​the carrier is 100-400 m². 2 / g, preferably 180-300m 2 / g; And / or, the pore volume of the carrier is 0.4-1.3 mL / g, preferably 0.5-1.2 mL / g; And / or, the pore diameter of the carrier is 4-13 nm, preferably 8-12 nm.

4. The catalyst according to claim 1 or 2, wherein, The alumina exists as γ-Al2O3; And / or, based on the total amount of the carrier, the content of alumina is 70-99% by weight and the content of titanium oxide is 1-30% by weight; Preferably, based on the total amount of the carrier, the content of alumina is 75-96% by weight and the content of titanium oxide is 4-25% by weight.

5. The catalyst according to claim 1 or 2, wherein, Based on the total amount of the catalyst, and calculated as oxides, the content of the Group VIII metal element is 0.5-10% by weight, preferably 1.5-5% by weight, the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight, and the content of the additive is 0.1-10% by weight. Preferably, the Group VIII metallic element is cobalt and / or nickel; Preferably, the Group VIB metal element is molybdenum and / or tungsten.

6. A method for preparing a hydrogenation catalyst for coal liquefaction, wherein, The method includes the following steps: (1) A gelling reaction is carried out between an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum to obtain a solid gelling product; (2) In the presence of a precipitant, the solid gelling product obtained in step (1) is subjected to an aging reaction to obtain an aging reaction product. (3) The aging reaction product obtained in step (2) is subjected to hydrothermal treatment and then subjected to first drying to obtain titanium-containing pseudoboehmite. The temperature of hydrothermal treatment is higher than the temperature of aging reaction. (4) The titanium-containing pseudoboehmite obtained in step (3) is optionally shaped, and then subjected to a second drying and a first calcination to obtain a carrier, wherein the carrier is a composite oxide containing alumina and titanium oxide, wherein the titanium oxide exists in the form of anatase, and the first calcination is carried out in a water-containing atmosphere. (5) The active metal and the additive are introduced onto the carrier obtained in step (4), and then a third drying and a second calcination are performed; the active metal includes a group VIII metal element and a group VIB metal element, and the additive is selected from at least one of phosphorus, silicon and fluorine; the second calcination is performed under vacuum conditions.

7. The method according to claim 6, wherein, In step (1), the acidic aluminum-containing and titanium-containing solutions are prepared by dissolving a titanium-containing compound in an acidic aluminum solution; Preferably, the titanium-containing compound is selected from at least one of titanium oxysulfate, titanium sulfate, and metatitanic acid; Preferably, the acidic aluminum solution is selected from at least one of aluminum sulfate solution, aluminum nitrate solution, and aluminum chloride solution; Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as aluminum oxide, is 35-120 g / L. Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium, calculated as titanium oxide, is 5-80 g / L.

8. The method according to claim 6 or 7, wherein, In step (1), the aluminum-containing alkaline solution is a sodium aluminate solution and / or a potassium aluminate solution; Preferably, in step (1), the concentration of the aluminum-containing alkaline solution, calculated as alumina, is 20-300 g / L; Preferably, the amounts of the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are such that, based on the total amount of the carrier, the content of aluminum oxide is 70-99% by weight, preferably 75-96% by weight, and the content of titanium oxide is 1-30% by weight, preferably 4-25% by weight.

9. The method according to claim 6 or 7, wherein, In step (1), the temperature of the aging reaction is 5-50°C higher than the temperature of the gelation reaction, preferably 10-30°C higher; Preferably, in step (1), the conditions for the gelation reaction include: a temperature of 40-80℃ and a pH value of 3-7; Preferably, in step (1), the conditions for the gelation reaction include: a temperature of 50-70°C and a pH value of 4-7.

10. The method according to claim 6 or 7, wherein, In step (2), the precipitant is selected from alkali metal compounds, preferably from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; Preferably, in step (2), the conditions for the aging reaction include: a temperature of 60-98°C, a time of 4-9 hours, and a pH value of 7-11. More preferably, in step (2), the conditions for the aging reaction include: a temperature of 70-95°C, a time of 5-8 hours, and a pH value of 7.5-10.

11. The method according to claim 6 or 7, wherein, The temperature of the hydrothermal treatment is 10-100°C higher than the temperature of the aging reaction, preferably 10-80°C higher, and more preferably 20-70°C higher. Preferably, in step (3), the conditions for hydrothermal treatment include: a temperature of 100-180℃ and a time of 2-9 hours; Preferably, no organic titanium-containing reagents are used in steps (1)-(3).

12. The method according to claim 6 or 7, wherein, In step (4), the conditions for the first calcination include: a temperature of 100-1000℃, a time of 1-10h, and a water-to-agent mass ratio of 0.1-10. Preferably, in step (4), the conditions for the first calcination include: a temperature of 300-650℃, a time of 2-6h, and a water-to-agent mass ratio of 0.5-3.5; Preferably, in step (4), the water-containing atmosphere also contains air, and the air flow rate is preferably 0.5-12 mL / (h·g), preferably 0.6-8 mL / (h·g), and more preferably 2-8 mL / (h·g).

13. The method according to claim 6 or 7, wherein, In step (5), the conditions for the second calcination include: a temperature of 350-1000℃, a time of 1-10h, and a vacuum degree of -0.1MPa to -10MPa; Preferably, in step (5), the conditions for the second calcination include: a temperature of 400-650℃, a time of 2-6h, and a vacuum degree of -0.1MPa to -3MPa.

14. The method according to claim 6 or 7, wherein, The amounts of Group VIII and Group VIB metal elements used in the prepared catalyst are such that, based on the total amount of the catalyst and calculated as oxides, the content of the Group VIII metal element is 0.5-10% by weight, preferably 1.5-5% by weight; the content of the Group VIB metal element is 5-35% by weight, preferably 6-30% by weight; and the content of the promoter is 0-10% by weight, preferably 0.1-10% by weight. Preferably, the Group VIII metallic element is cobalt and / or nickel; Preferably, the Group VIB metal element is molybdenum and / or tungsten.

15. The application of the catalyst according to any one of claims 1-5 or the catalyst prepared by the preparation method according to any one of claims 6-14 in the hydrotreating of coal liquefaction oil.

16. A method for hydrotreating coal liquefaction oil, wherein, The method includes: hydrogenating coal liquefaction oil in the presence of a catalyst and hydrogen, wherein the catalyst is the catalyst according to any one of claims 1-5 or the catalyst prepared by the preparation method according to any one of claims 6-14.

17. The method of claim 16, wherein, The reaction conditions include: a temperature of 200-420℃, a pressure of 2-18 MPa, a hydrogen-to-oil volume ratio of 50-5000, and a liquid hourly space velocity of 0.1-10 h⁻¹. -1 .

Citation Information

Patent Citations

  • Heavy distillate oil hydrotreating catalyst and application thereof

    CN109833891A

  • Hydrogenation catalyst, preparation method and application thereof

    CN113649016A